Improvement in the nutritional status after transcatheter aortic valve implantation. Issue 3 (September 2021) - Tobe, Akihiro; Tanaka, Akihito; Tokuda, Yoshiyuki; Akita, Sho; Miki, Yusuke; Furusawa, Kenji; Ishii, Hideki; Usui, Akihiko; Murohara, Toyoaki
Highlights: This study investigated the changes in the nutritional status after transcatheter aortic valve implantation (TAVI). The results suggested that the nutritional status of patients could improve after TAVI. Improvement was observed especially in the patients with low levels at baseline. Abstract: Background: A poor nutritional status of patients before transcatheter aortic valve implantation (TAVI) has been reported to be associated with poor clinical outcomes. However, changes in the nutritional status following TAVI have not been fully elucidated. Methods: In this single-center retrospective observational study, 129 patients whose nutritional status at baseline and 6 months after TAVI were available were investigated. The prognostic nutritional index (PNI) and geriatric nutritional risk index (GNRI) were used to assess the nutritional status of the patients at baseline and at 6 months. We further assessed changes in the nutritional status of patients in the subgroups stratified according to the baseline levels as low and high. Results: The PNI and GNRI values at 6 months were significantly better than at baseline [PNI, baseline: 44.5 (41.0–48.0), 6 months: 46.0 (41.9–48.3), p = 0.02; GNRI, baseline: 95.3 (89.0–100.3), 6 months: 97.8 (91.5–101.4), p = 0.006]. Both PNI and GNRI values at 6 months were significantly better in the patients with a low baseline nutritional status, while no significant change was observed in those with high baseline levels [PNI, low; baseline: 36.8 (36.1–39.4), 6 months: 40.8 (39.0–43.4), p = 0.002, high; baseline: 47.0 (43.0–49.5), 6 months: 46.5 (43.5–50.5), p = 0.44 and GNRI, low; baseline: 86.4 (81.7–88.7), 6 months: 88.6 (83.4–95.3), p = 0.001, high; baseline: 99.8 (95.3–102.8), 6 months: 100.7 (96.8–103.4), p = 0.34]. Conclusion: Nutritional status of patients might improve during the chronic phase after TAVI, especially in those with poor baseline levels.